Education trajectories in Ethiopia, India, Peru and Vietnam: From early childhood to early adulthood - Cueto, S; Singh, R; Woldehanna, T; Le, T; Miranda, A (Young Lives, 2016)
The Sustainable Development Goals approved in 2015 include provisions around education, such as SDG 4 (United Nations Organization 2015). These are related to lifelong learning, and include both access and outcomes (learning) for all children. Monitoring to what level children reach these goals and what factors are associated with their progress is therefore an important research and policy issue. In this policy brief, we describe the educational trajectories of 12,000 children in total, across two cohorts: the Younger Cohort born around 1994 and the Older Cohort born around 2001, in Ethiopia, India, Peru and Vietnam. The data come from Young Lives household and school surveys conducted over the last 15 years.